Keeping Quality of Shell Eggs During Summer - Radhakrishnan Nair R (Department of Poultry Science, College of Veterinary Science, 1981)
A study was conducted to asses the keeping quality of shell eggs during summer months of March, April and May. Quality deterioration on 3rd, 5th, 7th, 10th and 15th days of storage of eggs held at room temperature was measured. Simulteniuosly lime treated eggs at room temperature and eggs held in cooler at 10 to 130 C were also evaluated similarly. A total of 432 tables eggs were used for the study, 144 eggs under each treatment. The traits measured for quality assessment were weight loss, albumen index, yolk index, haugh unit score, per cent thick albumen and albumen pH.